Simulation and Observations of Stratospheric Aerosols from the 2009 Sarychev Volcanic Eruption - Kravitz, B.; Robock, A.; Bourassa, A.; Deshler, Terry; Wu, D.; Mattis, I.; Finger, F.; Hoffmann, A.; Ritter, C.; Bitar, L.; Duck, T. J.; Barnes, J. E. (Journal of Geophysical Research, 2011)
©2011 by the American Geophysical Union. We used a general circulation model of Earth's climate to conduct simulations of the 12-16 June 2009 eruption of Sarychev volcano (48.1°N, 153.2°E). The model simulates the formation and transport of the stratospheric sulfate aerosol cloud from the eruption and the resulting climate response. We compared optical depth results from these simulations with limb scatter measurements from the Optical Spectrograph and Infrared Imaging System (OSIRIS), in situ measurements from balloon-borne instruments lofted from Laramie, Wyoming (41.3°N, 105.7°W), and five lidar stations located throughout the Northern Hemisphere. The aerosol cloud covered most of the Northern Hemisphere, extending slightly into the tropics, with peak backscatter measured between 12 and 16 km in altitude. Aerosol concentrations returned to near-background levels by spring 2010. After accounting for expected sources of discrepancy between each of the data sources, the magnitudes and spatial distributions of aerosol optical depth due to the eruption largely agree. In conducting the simulations, we likely overestimated both particle size and the amount of SO2 injected into the stratosphere, resulting in modeled optical depth values that were a factor of 2-4 too high. Modeled optical depth due to the eruption shows a peak too late in high latitudes and too early in low latitudes, suggesting a problem with stratospheric circulation in the model. The model also shows a higher decay rate in optical depth than is observed, showing an inaccuracy in stratospheric removal rates in some seasons. The modeled removal rate of sulfate aerosols from the Sarychev eruption is higher than the rate calculated for aerosols from the 1991 eruption of Mt. Pinatubo.